Relevansi Prinsip-Prinsip Pendidikan Psikologis dan Tujuan Pendidikan Islam Berbasis Al-Qur'an dan Hadist - Kusmawaty Matara (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to find the relevance between the principles of psychological education and the goals of Islamic education based on the Qur'an and hadith. For this reason, the data we get is sourced from scientific findings from psychology and Islamic education experts from various sources, books, and scientific articles. We have studied all of that carefully under a phenomenological approach, an approach to collecting as much data as possible to find something phenomenal in this case that can answer the problems and hypotheses of this study. Therefore, based on this study and the discussion of these two variables, we find that there is very little significant relevance between the principles of psychological education and the goals of Islamic education based on the Qur'an and other sources that are believed to have relevance to the two variables above. It is hoped that these findings will become necessary inputs in supporting similar studies in the future, and this study will become input for the implementation of improving education, psychology, and Islamic religious studies.